2023
DOI: 10.3390/ijms24054509
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Models to Study Epithelial-Mesenchymal Transition in Proliferative Vitreoretinopathy

Abstract: Proliferative vitreoretinal diseases (PVDs) encompass proliferative vitreoretinopathy (PVR), epiretinal membranes, and proliferative diabetic retinopathy. These vision-threatening diseases are characterized by the development of proliferative membranes above, within and/or below the retina following epithelial-mesenchymal transition (EMT) of the retinal pigment epithelium (RPE) and/or endothelial-mesenchymal transition of endothelial cells. As surgical peeling of PVD membranes remains the sole therapeutic opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…RPE cell migration is a crucial step in the formation of proliferative membranes in PVR. 27 , 28 During the PVR formation, RPE cells first detach from Bruch's membrane and migrate to the epi-retinal or sub-retinal spaces where they interact with other cellular components and the extracellular matrix to form the proliferative membrane. 7 , 8 In our study, both scratch assay and transwell assay demonstrated that silibinin significantly inhibited the migration of RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…RPE cell migration is a crucial step in the formation of proliferative membranes in PVR. 27 , 28 During the PVR formation, RPE cells first detach from Bruch's membrane and migrate to the epi-retinal or sub-retinal spaces where they interact with other cellular components and the extracellular matrix to form the proliferative membrane. 7 , 8 In our study, both scratch assay and transwell assay demonstrated that silibinin significantly inhibited the migration of RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascular age-related macular degeneration (nAMD) also develops membranes, similar to PVDs’ membranes, but the trigger for this pathology mainly consists of inflammation or oxidative stress. 1 …”
Section: Introductionmentioning
confidence: 99%
“…Neovascular age-related macular degeneration (nAMD) also develops membranes, similar to PVDs' membranes, but the trigger for this pathology mainly consists of inflammation or oxidative stress. 1 It has already been proven that retinal pigment epithelial (RPE) cells are deeply involved in PVDs' development, stimulated by cytokines or growth factors released as a consequence of the trigger events. 2 In particular, RPE cells, that in healthy condition are subjected to contact inhibitory effect and have a very low turnover rate, under a stimulatory event, for example retinal detachment in PVR, improve their proliferative and migratory properties, and undergo morphological changes, losing their cellular polarity and assuming a fibroblastoid appearance, leading to the so-called epithelial-mesenchymal transition (EMT).…”
Section: Introductionmentioning
confidence: 99%